2023
DOI: 10.1021/acs.est.2c07796
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Organophosphate Esters by Rice and Rhizosphere Microbiome: Multiple Metabolic Pathways, Mechanism, and Toxicity Assessment

Abstract: The biotransformation behavior and toxicity of organophosphate esters (OPEs) in rice and rhizosphere microbiomes were comprehensively studied by hydroponic experiments. OPEs with lower hydrophobicity were liable to be translocated acropetally, and rhizosphere microbiome could reduce the uptake and translocation of OPEs in rice tissues. New metabolites were successfully identified in rice and rhizosphere microbiome, including hydrolysis, hydroxylated, methylated, and glutathione-, glucuronide-, and sulfate-conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…BEHPP (C 22 H 39 O 4 P, m / z 399.26531, RT = 14.16 min) is structurally similar to 2-ethylhexyl diphenyl phosphate (EHDPP) and was identified with fragments of 57.07001 (C 4 H 9 , −7.277 ppm), 95.04929 (C 6 H 7 O, −4.206 ppm), and 175.01534 (C 6 H 8 O 4 P, −3.886 ppm) (Figure S14). Abundant BEHPP has been detected in various environmental matrices, including air, soil, dust, lake sediment, as well as rice, and wild fish . Nevertheless, BEHPP was detected in the indoor environment with DFs of 50 and 90% in the air and dust samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BEHPP (C 22 H 39 O 4 P, m / z 399.26531, RT = 14.16 min) is structurally similar to 2-ethylhexyl diphenyl phosphate (EHDPP) and was identified with fragments of 57.07001 (C 4 H 9 , −7.277 ppm), 95.04929 (C 6 H 7 O, −4.206 ppm), and 175.01534 (C 6 H 8 O 4 P, −3.886 ppm) (Figure S14). Abundant BEHPP has been detected in various environmental matrices, including air, soil, dust, lake sediment, as well as rice, and wild fish . Nevertheless, BEHPP was detected in the indoor environment with DFs of 50 and 90% in the air and dust samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…BEHPP S14). Abundant BEHPP has been detected in various environmental matrices, including air, 62 soil, 24 dust, 23 lake sediment, 17 as well as rice, 88 and wild fish. 89 Nevertheless, BEHPP was detected in the indoor environment with DFs of 50 and 90% in the air and dust samples, respectively.…”
Section: Identification Of Nopsmentioning
confidence: 99%
“…The procedures of sample extraction and purification have been described in other references [ 48 ] and were used with some modifications. The soil and plant samples were extracted with ultrasonic extraction (Supmile, Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Research on OPEs in crops is still in the early stages compared to research on their presence in soils. Yu [ 48 ] conducted a study on the biotransformation behavior and toxicity of OPEs through hydroponic experiments. The findings revealed that OPEs with lower hydrophobicity exhibited greater ease of translocation to the top.…”
Section: Introductionmentioning
confidence: 99%
“…The following criteria were used for transformation product identification: (1) peaks with intensity above threshold, (2) the presence in DTMDPB-amended enrichment culture and the absence or significantly lower levels in the control experiment with sterilized enrichment culture, and (3) a reasonable chemical formula derived from the exact mass (mass accuracy tolerance <5 ppm) and the isotopic pattern (≥80%). The confidence levels of those identified transformation products were determined according to previous studies. …”
Section: Methodsmentioning
confidence: 99%